2022
DOI: 10.1186/s40478-021-01303-6
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling in cerebral amyloid angiopathy reveals an overlap with CADASIL highlighting accumulation of HTRA1 and its substrates

Abstract: Cerebral amyloid angiopathy (CAA) is an age-related condition and a major cause of intracerebral hemorrhage and cognitive decline that shows close links with Alzheimer's disease (AD). CAA is characterized by the aggregation of amyloid-β (Aβ) peptides and formation of Aβ deposits in the brain vasculature resulting in a disruption of the angioarchitecture. Capillaries are a critical site of Aβ pathology in CAA type 1 and become dysfunctional during disease progression. Here, applying an advanced protocol for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 82 publications
(117 reference statements)
2
24
0
Order By: Relevance
“… 10 This phenomenon indicated that the fragility of the vascular wall may lead to not only thrombosis but also hemorrhage in this disease. In addition, recent studies found that HTRA1 colocalize with NOTCH3 deposits in the brain vessels of patients with CADASIL 26 and Aβ deposits in the capillaries of patients with cerebral amyloid angiopathy, 27 but no deposits of amyloid or granular osmiophilic material were observed in this case and the 2 previously reported cases. It still remains unclear how the HTRA1 mutations eventually cause cerebral small vessel dysfunction and how these hereditary CSVD-related genes interact with each other.…”
Section: Discussionsupporting
confidence: 59%
“… 10 This phenomenon indicated that the fragility of the vascular wall may lead to not only thrombosis but also hemorrhage in this disease. In addition, recent studies found that HTRA1 colocalize with NOTCH3 deposits in the brain vessels of patients with CADASIL 26 and Aβ deposits in the capillaries of patients with cerebral amyloid angiopathy, 27 but no deposits of amyloid or granular osmiophilic material were observed in this case and the 2 previously reported cases. It still remains unclear how the HTRA1 mutations eventually cause cerebral small vessel dysfunction and how these hereditary CSVD-related genes interact with each other.…”
Section: Discussionsupporting
confidence: 59%
“…It is interesting to compare our proteomic data with data reported in previous CAA proteomics studies. In two studies, the brain vessels were isolated from CAA frozen brains and used for proteomic analysis, but the COL6A family, which is directly involved in fibrosis, a typical CAA pathology, was not detected or was not increased in CAA vessels [ 10 , 64 ]. CAA vessels are very fragile and the vascular structure is disrupted during the process of vessel isolation.…”
Section: Resultsmentioning
confidence: 99%
“…A similar analysis in patients is currently not possible due to the lack of appropriate post mortem tissue. However, proteomic analyses of vessel samples derived from CAA and CADASIL patients revealed an unexpected link to HTRA1 providing further insight into its role in humans (Zellner et al, 2018(Zellner et al, , 2022.…”
Section: High Temperature Requirement Protein Amentioning
confidence: 99%
“…. (Zellner et al, 2018(Zellner et al, , 2022Kato et al, 2021). Evidence for an impairment of HTRA1-mediated proteolytic activity in the cerebrovasculature has so far only been found in patients carrying congenital mutations (Nozaki et al, 2014), thus HTRA1 inactivation via sequestration on a protein level would represent a novel pathomechanism (Figure 1).…”
Section: Mechanisms Of Htra Inactivationmentioning
confidence: 99%